2023
DOI: 10.1088/1674-1056/ac80b1
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the characteristic delay time in the leader-follower behavior in children single-file movement

Abstract: The single-file movement experiment offers a convenient way to investigate the one-dimensional leader-follower behavior of pedestrians. This study investigated the time delays of children pedestrians in the leader-follower behavior by introducing a time-dependent delayed speed correlation. A total of 118 German students from the fifth grade (aged 11-12 years old) and the 11th grade (aged 17-18 years old) participated the single-file experiment. The characteristic delay time for each pedestrian was identified b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In studies involving pedestrians, the time lag is typically referred to as the "visual-motor delay" and is generally assumed to be around 0.40 s [29,30]. The study by Dias et al [31] found that this characteristic time delay varies from 0.12 s to 0.68 s. However, a higher average delay time was reported by Xue et al [32] for the correlation between the speeds of children pedestrian pairs, where the average delay time ranged from 0.75 to 0.84 s. For micromobility vehicles, such as the Segway, the reaction time can be incorporated depending on the situation, e.g., when following a pedestrian or a cyclist and during normal following or sudden brake situations [33]. Dias et al [33] reported that the average reaction times (±SDs) of Segway riders were 0.50 s (±0.29 s) and 0.70 s (±0.44 s) when following a cyclist and a pedestrian, respectively, during sudden brake situations.…”
Section: Relationship Between Relative Speed and Accelerationmentioning
confidence: 97%
“…In studies involving pedestrians, the time lag is typically referred to as the "visual-motor delay" and is generally assumed to be around 0.40 s [29,30]. The study by Dias et al [31] found that this characteristic time delay varies from 0.12 s to 0.68 s. However, a higher average delay time was reported by Xue et al [32] for the correlation between the speeds of children pedestrian pairs, where the average delay time ranged from 0.75 to 0.84 s. For micromobility vehicles, such as the Segway, the reaction time can be incorporated depending on the situation, e.g., when following a pedestrian or a cyclist and during normal following or sudden brake situations [33]. Dias et al [33] reported that the average reaction times (±SDs) of Segway riders were 0.50 s (±0.29 s) and 0.70 s (±0.44 s) when following a cyclist and a pedestrian, respectively, during sudden brake situations.…”
Section: Relationship Between Relative Speed and Accelerationmentioning
confidence: 97%
“…Lu et al [14] uncovered the characteristics of pedestrian movement under different social distancing measures. Xue et al [15] investigated the one-dimensional leader-follower behavior of children. The study found that the revealed characteristic delay time of children depends on densities.…”
Section: Introductionmentioning
confidence: 99%